2014
DOI: 10.1038/ismej.2014.224
|View full text |Cite
|
Sign up to set email alerts
|

Sudden motility reversal indicates sensing of magnetic field gradients in Magnetospirillum magneticum AMB-1 strain

Abstract: Many motile unicellular organisms have evolved specialized behaviors for detecting and responding to environmental cues such as chemical gradients (chemotaxis) and oxygen gradients (aerotaxis). Magnetotaxis is found in magnetotactic bacteria and it is defined as the passive alignment of these cells to the geomagnetic field along with active swimming. Herein we show that Magnetospirillum magneticum (AMB-1) show a unique set of responses that indicates they sense and respond not only to the direction of magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Our results indicate a threshold drag of 9.5 pN, corresponding to a flow velocity of 550 µm s −1 , where magnetotaxis enables MTB to overcome counterdirectional flow. These findings are relevant to marine ecosystems, where both the direction of the geomagnetic field and the flow influence the orientation and, therefore, the migration of MTB.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our results indicate a threshold drag of 9.5 pN, corresponding to a flow velocity of 550 µm s −1 , where magnetotaxis enables MTB to overcome counterdirectional flow. These findings are relevant to marine ecosystems, where both the direction of the geomagnetic field and the flow influence the orientation and, therefore, the migration of MTB.…”
Section: Discussionmentioning
confidence: 79%
“…Several biological and physical factors may influence the response of MTB to the magnetic field and shear flow, including the hydrodynamic effects due to orientation of the cell body with respect to flow, the interaction of the dipole moment and the magnetic field, and the molecular composition of the cell such as intercellular protein content . With respect to biological factors, the interaction of methyl‐accepting chemotaxis protein (MCP) and the filamentous cytoskeletal protein MamK is suggested to play an important role in magnetotactic behavior of M. magneticum AMB‐1, particularly at low magnetic field strength (≈1 mT) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon further explains why the cells possessing amb0994 can be active in sensing the external fields to coordinate their motions, rather than being completely passive to orientation. Another study revealed that M. magneticum AMB-1 cells could sense magnetic field gradients and respond to them by reversing direction (González et al, 2015 ). The author speculates that this difference in the field could be torqueing the cells and relaying this signal to Amb0994.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon further explains why the cells possessing amb0994 can be active in sensing the external fields to coordinate their motions, rather than being completely passive to orientation. Another study revealed that M. magneticum AMB-1 cells can sense magnetic field gradients and respond to them by reversing direction [59]. The author speculates that this difference in the field could be torqueing the cells and relaying this signal to Amb0994.…”
Section: Discussionmentioning
confidence: 99%